Functionally Graded Piezoelectric Plates in Cylindrical Bending by Semi-analytical Approach - Sameer Sawarkar; Sandeep Pendhari (Mechanics of Advanced Composite Structures)
A simply supported (SS) functionally graded piezoelectric material (FGPM) plate in a 2D domain has been analyzed for stress and displacement by a Semi-analytical approach. In-plane variation in stresses and displacements is assumed to be trigonometric. The elasticity approach is used and no simplifying assumption is made on the stress and displacement fields in the through-thickness direction. The FGPM plate is subjected to a transverse electro-mechanical load whose intensity remains constant in the out-of-plane direction. Thus, the plate is under plane stress and plane strain conditions of elasticity. Exponential law or power law has been considered for smooth gradation of material properties in the through-thickness direction. The formulation is a set of first-ordered ordinary differential equations (ODE), which has been solved using numerical integration. Exact outcomes in the literature have been used to correlate and validate the present model results. Additional investigation has been carried out on FGPM plates and beams and results are provided for future reference.